Greening the agriculture sector of Uzbekistan: Costs of inaction, benefits of action, and returns on investment to combat degradation in land, water, and forest resources - Yigezu, Yigezu; Nurbekov, Aziz; Akramkhanov, Akmal; Nazarkulov, Umidjan; Ganiev, Akmaljon; Vogl, Adrian; Sarmiento, Jorge; Agostini, Paola; S. Golub, Elena; M. Piabuo, Serge (2025)
This report is based on a comprehensive study which analyzed the drawbacks of the current brown economic growth model that is followed in the agriculture, forest, and water sectors of Uzbekistan. The study also estimated the total economic costs of degradation in the three main forms of natural capital, namely crop & pasture lands, forests, and water in the country. While there exist some past studies which made attempts to estimate the total cost of land degradation in Uzbekistan, this study tried to make improvements on several fronts: 1) unlike past studies which were limited either thematically, geographically or in scale, this study considers and attempts to provide estimates of all degradation-induced losses of ecosystem service provisions and their associated economic losses covering the three main capitals and all three biomes (crops/pasture, forests, and water); 2) Methodologically, it makes improvements by first generating per unit-area estimates which were then aggregated to the level of each province, and finally to the national level using appropriate weights (mostly land area under each biome). Such estimates are important in informing provincial and national governments’ policy actions and priority setting; 3) It is based on a theoretically sound and consistent method that can be applied to all dimensions of losses which are induced by the degradation of all natural capitals; 4) The study used official statistics, published and unpublished research findings, and systematically solicited expert estimates on important variables to generate new estimates or make useful extrapolations for parameters necessary for some of the components of degradation-induced losses for which no provincial or national estimates existed; 5) Every effort was made to document all theoretical underpinnings, the procedures and models used, data sources, and simplifying assumptions made during estimation, that are expected to be useful in providing the reader the context under which these estimates are made. Acknowledging that some of the parameters and assumptions made could be contentious, the report aimed at providing conservative estimates of the total cost of degradation in natural capitals in the agriculture, forest, and water sectors of Uzbekistan.